FRI0162 IL-9 Over-Expression and Th9 Polarization Immunologically Characterizes the Subclinical Gut Inflammation of Patients with Psoriatic Arthritis. (10th June 2014) - Ciccia, F.; Ferrante, A.; Rizzo, A.; Rodolico, V.; Guggino, G.; Raimondo, S.; Bignone, R.; Peralta, S.; Alessandro, R.; Triolo, G.
Abstract : Background: Subclinical gut inflammation has been demonstrated in patients with psoriatic arthritis (PsA) suggesting a role for the gut in the pathogenesis of inflammation in these patients. A key role for the IL-23, IL-17, IL-22 and IL-9 in the pathogenesis of psoriasis and psoriatic arthritis has been suggested, the immunologic abnormalities underlying subclinical gut inflammation in PsA are still undefined however. Objectives: This study was undertaken to investigate the expression and tissue distribution of IL-23 and of Th17, Th22 and Th9 related molecules in the subclinical gut inflammation of patients with PsA. Methods: Gut inflammation was assessed accordingly to De Vos et al (1). Quantitative gene expression analysis of Th1, IL-23/Th17, Th22 and Th9 responses was performed in intestinal biopsy samples obtained from 22 patients with PsA (12 with non-radiographic psoriatic axial SpA, 5 of them displaying HLA-27 positivity), 10 patients with HLA-27 positive-ankylosing spondylitis (AS), 10 patients with Crohn's disease (CD) and 20 healthy controls. IL-23, IL-17, IL-22 and IL-9 tissue distribution was also evaluated by immunohistochemistry. Results: Chronic ileal inflammation was observed in 15 PsA patients with no difference regarding axial or peripheral disease. The terminal ileum of PsA patients was characterized by a complex immunological signature. IL-23p19 m-RNA was not significantly over-expressed compared to controls but a clear Th17 and Th22 polarized immune response was demonstrable, at levels comparable to those observed in CD. Differently from CD and similarly to AS, Th1 cytokines were not significantly over-expressed in PsA. Conversely, a strong IL-23p19 and IL-22 expression in the absence of Th17 polarization was confirmed in AS gut. Unlike AS and CD, a strong and significant up-regulation of IL-9 immunologically characterized the gut of PsA patients. In particular, IL-9 immune-reactivity was observed among infiltrating mononuclear cells, high endothelial venules and Paneth cells. IL-9 mononuclear cells were demonstrated to be in large part Th9 cells. IL-9 over-expression was accompanied by significant Paneth cells hyperplasia. Conclusions: The strong IL-9/Th9 polarization seems to be the predominant immunological signature of subclinical gut inflammation in PsA. Our findings indicate however a complex immune-regulation occurring in the gut of PsA patients where Th17 and Th22 polarization seems also to occur. References: De Vos M, Cuvelier C, Mielants H et al. Ileocolonscopy in seronegative SPondiloarthropathy. Gastroenterology 1989 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5174